Ability Antioxidant and Anti-inflammatory Phycocyanin from Extract Spirulina platensis - Rahma, Diny Hazita; Armaini, Armaini; Syafrizayanti, Syafrizayanti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Increased exposure to free radicals and chronic inflammatory processes are major factors in the development of various degenerative diseases, including cancer, diabetes, and cardiovascular disease. Therefore, the search for natural bioactive compounds with antioxidant and anti-inflammatory properties has become a major focus in pharmaceutical and biomedical research. Phycocyanin is a complex protein pigment from the microalgae Spirulina platensis which is known to have biological activities, especially as an antioxidant and anti-inflammatory. This study aims to evaluate the antioxidant and anti-inflammatory properties of phycocyanin extract obtained through maceration and freeze-thawing methods using PBS solution pH 7.4 and distilled water. Antioxidant activity was evaluated using the ABTS (2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonate)) method, while the anti-inflammatory potential was tested using the protein denaturation inhibition method. The test results showed that the phycocyanin extract had quite strong antioxidant activity with an IC₅₀ value of 82.86 mg/L. In addition, anti-inflammatory activity was also shown with an IC₅₀ value of 73.92 mg/L in the protein denaturation inhibition test. These results indicate that phycocyanin extract from Spirulina platensis has the potential as a natural bioactive agent in the development of nutraceutical, cosmetic, and pharmaceutical products. Further studies are needed to understand the molecular mechanisms and in vivo testing to support its clinical application.